Tinjauan Pustaka Mengenai Dampak Pengelolaan Rugi Laba Terhadap Kinerja Keuangan Rumah Sakit: Sudut Pandang Manajerial - Sherly Firsta Rahmi Rahmi; Nur Husna Dewi; Budi Hartono; Alfani Ghutsa Daud (Journal of Innovative and Creativity, 2025)
The management of income statements is a crucial aspect in strategic decision-making within hospitals. The study aims to analyze the impact of income statement management on hospital financial performance from a managerial perspective. Using a literature review approach based on 20 national and international journals, the study concludes that a proper understanding and utilization of income statement can enhance operational efficiency, support effective resource allocation and strengthen strategic planning. From a managerial standpoint, the income statement functions as a tool for monitoring and evaluating the performance of work units. Furthermore, it serves as a basis for both short- and long-term financial decision-making. The study also highlights that hospital management teams who actively utilize this report tend to exhibit more stable and sustainable financial performance. Lastly, it emphasizes the importance of strengthening hospital management capacity in effectively managing and utilizing financial information to support the success of healthcare service delivery.